The Role of School Principal Management in Talent Interest Mapping: A Case Study of Human Resource Vocationalization at Automotive Vocational School Kulon Progo - Anang Eko Saputro; Widodo Widodo; Arif Bintoro Johan (VANOS Journal of Mechanical Engineering Education, 2024)
The management role of school principals is very important, especially in improving the quality of education, one of which is mapping interest and talent, especially as there are still many students who are confused about recognizing their own potential, which will later influence a lack of preparation and result in many vocational school students not being absorbed into work after graduating. The aim of this research is to find out the role of school principal management in mapping talent interests as an effort to vocationalization human resources. The research method uses a qualitative case study approach design. Data were collected through observation, in-depth interviews from each key source including 4 key sources (Principal, Head of automotive Program and students). Data analysis using The Miles and Huberman model was added with NVivo 12 Plus software by identifying, evaluating and describing data. The results of research on the management role of school principals include creating programs in schools to facilitate the development of interests and talents, collaborative direction of teachers and school committees, increasing competency of education staff and students in schools to face current developments and create quality graduates.